Analyzing and Comparing the Association Between Control Policy Measures and Alcohol Consumption in Europe. (15th October 2014) - Baccini, Michela; Carreras, Giulia
Abstract : This paper focuses on the association between alcohol consumption and the introduction of control policy measures, within the AMPHORA 12 country European project. We estimated the "net" associations between intervention policies and total alcohol consumption, taking into account contextual socioeconomic factors and including all policies in the same regression model. The associations were estimated for each country, and the country-specific results were compared in a random-effects meta-analysis. The association between policy measures and total alcohol consumption was very heterogeneous among countries. Policies on restricting alcohol availability and on enhancing the minimum age for alcohol purchase appeared to be related to decreasing alcohol consumption. The evidence regarding the effect of the others kinds of interventions was more contradictory.